Interpersonal Communication of Da’i in Raising the Religious Awareness of Children in Conflict with the Law (ABH) - Yopi Kusmiati; Novia Hasan Pratiwi (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2023)
Currently there are many children who have to deal with the law, caused by cases of fights, robberies, murders. To deal with children who are affected by this case, a rehabilitation center is needed as a place for protection and education for children. Center for Social Rehabilitation of Children Requiring Special Protection “Handayani Jakarta” is a rehabilitation center that provides religious guidance as a method of rehabilitation for children involved in criminal cases. Religious Supervisors, in this case called da'i have an important role to choose the right communication in increasing children's religious awareness so they don't repeat their actions. This study aims to determine the interpersonal communication of preachers at BRSAMPK Handayani Jakarta and the interpersonal communication of preachers in increasing the religious awareness of children in conflict with the law. The theory used in this study is the theory of competence communication, while the method used is a qualitative method with a constructivist paradigm. Data collection techniques through direct observations, interviews, and document studies. The results of the study show that preachers in building interpersonal communication are by understanding children's character, fostering children's trust, providing guidance with a sense of humor, using language that is easy to understand and applying a firm attitude in guidance. In increasing ABH's religious awareness, the way of interpersonal communication used by da'i is to provide motivation, communicate persuasively, and conduct question and answer dialogue.